A prominent role for the IL1 pathway and IL15 in susceptibility to chronic cavitary pulmonary aspergillosis. (2nd April 2014) - Smith, N. L. D.; Hankinson, J.; Simpson, A.; Bowyer, P.; Denning, D. W.; Roilides, E.
Abstract Chronic cavitary pulmonary aspergillosis (CCPA) is a progressive lung condition with a 10–30% annual mortality. Although overtly immunocompetent, some immunogenetic defect in patients is likely. To investigate a possible immunogenetic defect in CCPA, we analysed biologically plausible candidate genes in 112 CCPA patients and 279 healthy controls in a genetic association study of genes involved in the post‐recognition immune response to Aspergillus fumigatus. We also compared gene expression in monocyte‐derived macrophages from subjects with and without disease, both at baseline and during stimulation with A. fumigatus. Compared with macrophages from healthy subjects, CCPA macrophages showed unrestrained rises in IL1A, IL1B, IL6, IRAK2 and TRAF6 throughout the experiment, and a lack of expression of TGFB1 at 9 h. Single nucleotide polymorphisms (SNPs) associated with CCPA were found in IL1B (n = 2), IL1RN and IL15 (n = 3). Uncontrolled expression of IL1 and IL6 and continuing high levels of these cytokines may result in continuing cellular influx and pro‐inflammatory responses, inhibiting disease resolution and contributing to disease progression in CCPA. The association of SNPs in IL1B, IL1RN and IL15 with CCPA supports a role for the IL1 pathway, as well as implicating the IL15 gene, in susceptibility to CCPA.